GASTRO INTESTINAL EFFECTS OF CROTON TIGLIUM IN EXPERIMENTAL ANIMALS - Pillai, N.R. (Medknow Publications & Media Pvt Ltd, 1999)
Croton tiglium used as a cathartic in Ayurvedic system of indigenous medicine, was investigated for its effects in experimental animals. 50% EtOH extract of the dried nuts of the plant was used of the study. The extract exhibited a dose dependent cathartic effect in albino rats, the extract also showed an increase to gut movement with an increased contractile movement on rabbit jejunum, partially blocked by atropine these preliminary findings suggest tat the ethanol extract of the croton dried nuts elicit a purgative effect by increasing the gut motility, partially via muscarnic receptor activation.